Effectiveness of intracuff alkalinized lidocaine associated with intravenous dexamethasone in reducing laryngotracheal morbidity in children undergoing general anesthesia for tonsillectomy: a randomized controlled trial - Oliveira, Morenna Ramos e [UNESP]; Modolo, Norma S.P. [UNESP]; Nascimento, Paulo [UNESP]; Lima, Rodrigo M.; Stirling, Devin; Mizubuti, Glenio B.; Silva, Leopoldo Muniz da; Navarro, Lais H. [UNESP] (Elsevier, 2024)
Background: Postoperative sore throat is one of the main postoperative complaints in patients undergoing tonsillectomy. As the primary outcome, we aimed to determine whether endotracheal tube cuffs filled with alkalinized lidocaine are associated with a lower incidence of postoperative sore throat and anesthesia emergence phenomena in children undergoing tonsillectomy or adenotonsillectomy. We also assessed the potential additional benefits of IV dexamethasone in reducing postoperative laryngotracheal morbidity. Methods: This is a clinical prospective, randomized, controlled trial. Patients were randomly allocated to one of four groups, as follows: air – endotracheal tube cuff filled with air; air/dex – endotracheal tube cuff filled with air and intravenous dexamethasone; lido – endotracheal tube cuff filled with alkalinized lidocaine; and lido/dex – endotracheal tube cuff filled with alkalinized lidocaine and intravenous dexamethasone. Perioperative hemodynamic parameters and the incidence of postoperative nausea and vomiting, coughing and hoarseness were recorded. Postoperative sore throat was assessed in the postanesthetic care unit and 24 hours post tracheal extubation. Results: In total, 154 children aged 4–12 years, ASA physical status I or II, undergoing general anesthesia for elective tonsillectomy and adenotonsillectomy, were assessed for postoperative sore throat in this study. The incidence of postoperative sore throat 24 hours after tracheal extubation was significantly lower in the lido/dex group compared to groups air and air/dex (p = 0.01). However, no additional reduction in these symptoms was observed from the intravenous administration of dexamethasone when comparing the lido and lido/dex groups. Similarly, there were no differences among groups regarding perioperative hemodynamic variables or postoperative nausea and vomiting, coughing, and hoarseness during the study period. Conclusion: Intracuff alkalinized lidocaine, associated with intravenous dexamethasone, might be effective in reducing sore throat 24 hours post-tonsillectomy or adenotonsillectomy in children when compared to the use of air as the cuff insufflation media.
Keywords: Endotracheal intubation; Lidocaine; Pediatrics; Sore throat; Tonsillectomy